Uso e aplicação de materiais poliméricos recicláveis na construção de um modelo molecular - Souza, Wlisses Guimarães (2012)
In the present paper, we propose the construction of a physical molecular model through the reuse of recyclable polymeric material, selected in units of selective garbage collect and in the school environment itself. This didactic intervention, especially in the Organic Chemistry classes, greatly helps the students have a threedimensional visualization of the molecules, averting itself, thus, the two-dimensional classicism of the whiteboard and the book. The construction of this handmade learning object has some extremely important characteristics both from an operational point of view of its elaboration as to the didactic point of view. Among them, we can quote: a very low cost; simplicity in the making and enforcement; a good approximation in the representation of the geometries of the molecules and the bond angles to the experimental values. The proposed model could substitute the ones sold on the market without any loss of information, moreover it adds some information that only this model is able to highlight, like the different size of the atoms. None of the representational physical models (either a model sold on the market or a handmade one) provides the discussion about the strength of the link. The model proposed here, however, has sticks with different length purposely, inducing the student to think about and verify the reason of this differentiation. Still regarding the process of learning, we can observe, in an workshop, that the involvement of the students in the making of the molecular kit favors their effective participation as an strategy and a way of a meaningful learning, functioning as a very efficient subsumptive. We still evidence the potential of this project in make the students sensible to the environmental consciousness, in view of the characteristics of the utilized material, indiscriminately discarded in the trash. Furthermore, some workshops were developed with teachers and students of the Public Educational System in the town of Arapiraca-AL. In the occasion, some quizzes were applied about the perception of the students and we observed, in most answers, that the use of the recycled material led to some discussions about what really trash is, this way what we’re going to do to minimize the problems caused by its consume and posterior discard and how to be rightly reused.